2011
DOI: 10.1167/iovs.10-6233
|View full text |Cite|
|
Sign up to set email alerts
|

Sclera-Choroid-RPE Transport of Eight β-Blockers in Human, Bovine, Porcine, Rabbit, and Rat Models

Abstract: Owing to the presence of pigment and drug binding, choroid-RPE is the principal barrier to transscleral β-blocker transport, with the barrier being more significant for lipophilic β-blockers. Although different in magnitude between species, sclera/SCRPE transport can be correlated between species. Tissue thickness accounts for the species differences in scleral transport. Differences in tissue thickness and melanin content largely account for the species differences in SCRPE transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 27 publications
4
44
0
Order By: Relevance
“…Likewise, Cruysberg et al (2002) have shown that the transscleral permeability of corticosteroids is related to molecular weight and lipid solubility with tissue transport of the most lipophilic molecule being the least and that of the least lipophilic molecule being the most. Consistent with our ␤-blockers transport studies across sclera-choroid-RPE in various species (Kadam et al, 2011), we observed that hydrophilic corticosteroids were transported better than lipophilic molecules during the course of the study (Figs. 2 and 3).…”
Section: Thakur Et Alsupporting
confidence: 89%
See 1 more Smart Citation
“…Likewise, Cruysberg et al (2002) have shown that the transscleral permeability of corticosteroids is related to molecular weight and lipid solubility with tissue transport of the most lipophilic molecule being the least and that of the least lipophilic molecule being the most. Consistent with our ␤-blockers transport studies across sclera-choroid-RPE in various species (Kadam et al, 2011), we observed that hydrophilic corticosteroids were transported better than lipophilic molecules during the course of the study (Figs. 2 and 3).…”
Section: Thakur Et Alsupporting
confidence: 89%
“…The bovine sclera and sclera-choroid-RPE transport study was conducted as described previously Thakur et al, 2010;Kadam et al, 2011). An isotonic assay buffer (pH 7.4) with the following composition was used during the entire tissue isolation procedure and transport study: 122 mM NaCl, 25 mM NaHCO 3 , 1.2 mM MgSO 4 , 0.4 mM K 2 HPO 4 , 1.4 mM CaCl 2 , 10 mM HEPES, and 10 mM glucose.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro transport studies across human cornea and sclera-choroid-RPE (SCRPE) were carried out according to a previously published method (Kadam et al, 2011) using the cassette dosing approach. A cassette of drug transporter substrates, including Gly-Sar (PEPT), L-tryptophan (ATB 0,+ ), MPP + (OCT), and phenylacetic acid (MCT) at a concentration of 100 mM in assay buffer was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro transport studies were carried out according to previously published method 28 . Due to very low solubilities (< 10 μg/ml) of celecoxib, CMA and CAA in water, 100 μg/ml solutions of these agents were prepared in assay buffer using 5% HPβCD.…”
Section: Methodsmentioning
confidence: 99%